2020
DOI: 10.3390/cells9040966
|View full text |Cite
|
Sign up to set email alerts
|

A Dense Fibrillar Collagen Scaffold Differentially Modulates Secretory Function of iPSC-Derived Vascular Smooth Muscle Cells to Promote Wound Healing

Abstract: The application of human-induced pluripotent stem cells (hiPSCs) to generate vascular smooth muscle cells (hiPSC-VSMCs) in abundance is a promising strategy for vascular regeneration. While hiPSC-VSMCs have already been utilized for tissue-engineered vascular grafts and disease modeling, there is a lack of investigations exploring their therapeutic secretory factors. The objective of this manuscript was to understand how the biophysical property of a collagen-based scaffold dictates changes in the secretory fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…However, collagen concentration had a greater impact on cell viability. This is consistent with our earlier report and can be attributed to the collagen fibrillar density (CFD) (Dash et al, 2020). The CFD increases with increasing concentration of collagen and impacts cell viability and proliferation.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…However, collagen concentration had a greater impact on cell viability. This is consistent with our earlier report and can be attributed to the collagen fibrillar density (CFD) (Dash et al, 2020). The CFD increases with increasing concentration of collagen and impacts cell viability and proliferation.…”
Section: Discussionsupporting
confidence: 94%
“…C. Dash, Z. Jiang, C. Suh, & Y. Qyang, 2015a; Gorecka et al, 2019). Most recently, our studies revealed the proangiogenic and anti-inflammatory potential of these cells and their use in the treatment of acute and chronic wounds (Dash et al, 2020; Gorecka et al, 2020). While these reports further confirm the future translational implications of hiPSC-VSMCs, we see an unmet need for a suitable delivery system for hiPSC-VSMCs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations